INFLUENCE OF FOREIGN DIRECT INVESTMENTS ON ECONOMIC DEVELOPMENT OF THE REPUBLIC OF SERBIA - Šušić, Milan (Journal of process management and new technologies, 2018)
The main intention of this paper is to point out the importance of foreign direct investment and their influence in the modern economy, as well as to explain possible ways of supporting foreign investments. The continuous process of integration of the world economy has led to a change in the attitude of recipient countries in relation to foreign direct investment. Such investment in developing countries is no longer viewed with suspicion and restraint, and controls and entry restrictions have been replaced by selective state policies to encourage their inflows. However, not all countries are equally successful in this, nor are the effects of foreign direct investment in all countries equal. The success of the chosen strategy depends primarily on the degree of overall social and economic development of the country. The ability of the government and domestic companies to optimally exploit the benefits that foreign direct investment brings. The paper examines the positive and negative effects of direct foreign investments on the economic development of Republic Serbia.